The Six Weeks' War : France : May 10 - June 25, 1940 - Draper, Theodore (GHQ,Rawalpindi Army Education Press, 1986)
A work of considerable background and insight, but largely for students of military and diplomatic affairs. A sober study, thoroughly researched and reasoned, of that short, sad saga of compromise and confusion and contradiction. The paradox of the French campaign which was to be based on a ""continuous front"" and ""unbroken fortifications"" and which was never more than a paper theory. Why was the Maginot Line not completed; what were the errors of the march into Belgium; of the French offensive-defensive which combined the weaknesses of both; the action -- day by day -- position by position, division by division. And the politics behind the civilian and military blunders the defeatists, the dualistic Reynaud, the use of Petain as cover, and the war between the defeatists and anti-defeatists with de Gaulle the spokesman of the latter. Then the Belgian capitulation and the question of Leopold's integrity; Dunkerque, which finished the French and brought the British to life; the fall of Paris, the new capital and the new government. And in recapitulation, the diplomatic and military lessons to be derived. A thoughtful and provocative book, but not for the man in the street.
Include Maps and Appendices
This book has been reproduced for Army Education Press by Pap-Board Printers Ltd., Rawalpindi (Pakistan) on behalf of Ferozsons Ltd., Lahore (Pakistan) under the authority of the Publisher of this book.
Keywords: World War (1939-1945) -- France